Incorporation of ZnO encapsulated MoS2 to fabricate flexible piezoelectric nanogenerator and sensor. (November 2022) - Cao, Shuoang; Zou, Haojie; Jiang, Bei; Li, Meilin; Yuan, Quanping
Abstract: Polymer based piezoelectric composite has attracted much attention in recent years due to its applicability in the manufacture of piezoelectric nanogenerators and sensors, high piezoelectric performance, high flexibility and easily shaping properties. In this work, ZnO with good piezoelectric properties was grown on the exfoliated MoS2 nanosheets by employing in situ polymerization, which was then incorporated in PVDF to prepare PVDF/MoS2 @ZnO piezoelectric composite film. The effect of various contents of ZnO on its structure and properties was emphatically discussed, as well as the mechanical energy collection and sensing performance. The results show that ZnO has been deposited on the surface of MoS2 nanosheet to form heterostructure (MoS2 @ZnO), as well as that the MoS2 @ZnO can effectively promote the transformation from α phase to β phase in PVDF, by which the content of β phase can be increased from 6.2 ± 2.5 % to 54.3 ± 2.7 %. It also exhibits excellent mechanical performance and flexibility with the tensile strengthen of 37.64 ± 5.12 MPa and elongation at break of 9.77 ± 1.57 %. The longitudinal piezoelectric constant ( d 33 ) of the composite film reached a maximum value of 31 ± 4 pC·N -1 . The open-circuit voltage (VOC ) and short-circuit current (ISC ) of PVDF/MoS2 @ZnO piezoelectric composite film reach as high as 6.22 V and 528 nA under the acting force of 100 KPa, respectively. It can charge a 1.0 μF commercial capacitor to 1.81 V in 400 s. Finally, a flexible piezoelectric sensor was fabricated to collect the pressure signals induced from human body movement (the bending of fingers, wrists and elbow joints), presenting excellent sensitive piezoelectric response with the VOC of about 0.41 V, 0.22 V and 0.32 V, respectively. The found performance indicates its feasibility for the application in wearable intelligent devices. Graphical Abstract: ga1 Highlights: ZnO grows on the MoS2 nanosheets to form heterogeneous structure. MoS2 @ZnO nanocomposite can transform α phase to β phase in PVDF. Flexible PVDF/MoS2 @ZnO composite film exhibits excellent mechanical and piezoelectric properties. PVDF/MoS2 @ZnO PENG can collect mechanical energy in the environment and human body movement.